The DIETARY CONCEPTS, PATTERNS AND LIFESTYLES IN ADULTS WITH DIABETES IN PUNJAB, PAKISTAN. - Faran Khan; Dr. Anam Yasmeen; Marriam Ahmad; Sheeza Imtiaz; saima Bano; Sara Yasien (International Journal of Pharmacy & Integrated Health Sciences)
Background: It is estimated that 1.5 million fatalities were directly caused by diabetes and 2.2 million deaths were caused by high blood glucose. This study was conducted to evaluate the link of food concepts, lifestyle habits, and dietary patterns among persons with diabetes mellitus. Methodology: The participants with diabetes mellitus were chosen from the diabetic wards and OPDs of several hospitals in Punjab. There were 600 participants in the entire sample size. The questionnaire was created to evaluate diabetes-related myths about food, diabetes-related lifestyle routines, and eating habits among persons with diabetes. Statistical techniques were used percentages (%) and cross tabs. Results: The study found that 55.8% of persons have a history of diabetes mellitus in their families. A sedentary lifestyle and lack of physical activity were prevalent in about 41.8% of the population. Participants with no education or little education have higher levels of uncontrolled HbA1C than participants with some education. 24% of the individuals who lacked education thought that eating too much sugar could cause diabetes. 10% of individuals actually used a home remedy, whereas 88.8% of participants did not use any. Of the participants, 24.5% believed that home remedies were helpful in managing diabetes. Conclusion: This study shows that people do not exercise enough; about half of the participants are physically inactive. Major meals were consumed in an appropriate amount. The promotion of good eating and lifestyle practices, particularly prevention among high-risk groups, is encouraged through health education and other interventions.